PETA PREVALENSI GANGGUAN AKIBAT KEKURANGAN YODIUM (GAKY) DI KOTA PADANG TAHUN 2006 - Zulkarnain Agus (Jurnal Kesehatan Masyarakat Andalas, 2007)
Iodine Deficiency Disorders (IDD) are symptoms can prominence because of deficiency iodine in a long period, specially influenced by environment factors where land water in that area are poor of iodine, especially in montinous area In contras, Padang is a coastal area of West Sumatera province but has a high prevalence of IDD. National mapping of IDD figures that Total Goiter Rate (TGR) in Padang district increased during the last 8 years, it was increased from 8.5 % in 1998 to 21.6 % in 2003. The objectives of the study were to know goiter prevalence among the schoolchildren based on thyroid gland palpation. This study was an observational study with cross sectional design and conducted in all subdistrict . Samples i this study were design as cluster sampling, where 3 primary school in each subdistric were selected by epidemiological recommendation as coastal and hinterland area, traditonal and modern villages. There were 3419 schoolchildren from 8 to 12 years old from 11 subdistricts of Padang. The goiter prevalence data collected by using palpation method and conducted by trained health center doctors. Based on this data collection, total goiter rate was 26.4 %, it was increased about 23.9 % from 21.6 in 2003 to 26.4 % in 2006. The prevalence of TGR was high in 3 sub districts, it was more than 30 % or severe endemic areas, namely as Bungus Teluk Kabung, Koto Tangah and Kuranji subdsitricts. There was no significant different of TGR prevalence between coastal and hinterland areas, but the significant different of TGR prevalence were showed between TGR of schoolcheldren in area of traditional and modern or new villiges TGR of traditional villiges was 43.9 %, while in modern or new villiges was only 18.1 %.